The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s10654-016-0179-x
|View full text |Cite
|
Sign up to set email alerts
|

A priori and a posteriori dietary patterns at the age of 1 year and body composition at the age of 6 years: the Generation R Study

Abstract: Dietary patterns have been linked to obesity in adults, however, not much is known about this association in early childhood. We examined associations of different types of dietary patterns in 1-year-old children with body composition at school age in 2026 children participating in a population-based cohort study. Dietary intake at the age of 1 year was assessed with a food-frequency questionnaire. At the children’s age of 6 years we measured their body composition with dual-energy X-ray absorptiometry and we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 39 publications
(72 reference statements)
2
25
1
Order By: Relevance
“…The lack of association between diet, obesity and dental caries in the present study is unsurprising given the inconsistent findings reported previously from investigations of both a priori and a posteriori-derived dietary patterns and measures of weight status [21,38,46,47,48] and dental caries [49,50,51,52] in early life. A possible explanation for the lack of association seen in the present study is that it may be too early to detect the influence of poor diet.…”
Section: Discussioncontrasting
confidence: 79%
“…The lack of association between diet, obesity and dental caries in the present study is unsurprising given the inconsistent findings reported previously from investigations of both a priori and a posteriori-derived dietary patterns and measures of weight status [21,38,46,47,48] and dental caries [49,50,51,52] in early life. A possible explanation for the lack of association seen in the present study is that it may be too early to detect the influence of poor diet.…”
Section: Discussioncontrasting
confidence: 79%
“…Population-specific dietary patterns were also extracted a posteriori, using the principal component analysis and reduced rank regression methods. First, the food items assessed with the FFQ were classified according to 27 food groups (Supplementary Table 1) based on previous studies, 22,26 but with adjustments to reflect characteristics of infant feeding practices potentially relevant in the context of celiac disease (eg, distinction between dairy products and formula-feeding or breastfeeding). Subsequently, principal component analysis was performed on those food groups to extract the dietary components that explained the largest amount of variance in food intake.…”
Section: Impactmentioning
confidence: 99%
“…Given the complexity of the human diet and the strong interactions between intake of different foods and nutrients, measuring overall dietary patterns is recommended as a complementary approach to measuring the intake of only single foods or nutrients [ 5 , 6 ]. One way to study overall diet is by predefined diet quality scores, which are usually based on dietary guidelines [ 5 , 7 ]. Although the use of diet quality indices in children has increased over the past years, Marshall et al suggested in their systematic review that more prospective cohort studies evaluating diet quality in children and its impact on health are needed [ 8 ].…”
Section: Introductionmentioning
confidence: 99%